2005
DOI: 10.1017/s0266467405002361
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in abundance and diversity of butterflies in Bornean rain forests: opposite impacts of logging recorded in different seasons

Abstract: We used traps baited with fruit to examine how the temporal variation of butterflies within primary forest in Sabah, Borneo differed between species. In addition, we compared patterns of temporal variation in primary and selectively logged forest, and we tested the hypothesis that selective logging has different recorded impacts on species diversity of adults during the wet monsoon period and the drier remaining half of the year. Species of Satyrinae and Morphinae had significantly less-restricted flight perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 50 publications
7
74
2
2
Order By: Relevance
“…Our findings are congruent with the wisdom that seasonal variation in abundance, species richness and diversity are common among tropical lepidopterans (DeVries et al 1997(DeVries et al , 1999Intachat et al 2001;Hamer et al 2005). Our earlier study (Skippari et al 2009) and that of Molleman et al (2006) both showed temporal fluctuations in lepidopteran abundance, diversity and species richness in Kibale.…”
Section: Seasonality In Herbivory Larval Density and Species Diversitysupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are congruent with the wisdom that seasonal variation in abundance, species richness and diversity are common among tropical lepidopterans (DeVries et al 1997(DeVries et al , 1999Intachat et al 2001;Hamer et al 2005). Our earlier study (Skippari et al 2009) and that of Molleman et al (2006) both showed temporal fluctuations in lepidopteran abundance, diversity and species richness in Kibale.…”
Section: Seasonality In Herbivory Larval Density and Species Diversitysupporting
confidence: 91%
“…However, sampling effort has not always been controlled, which makes comparison of the results difficult (Koh 2007). Furthermore, seasonal variation in communities has only seldom been taken into account although variation in diversity of butterflies exists in temporal scale (DeVries et al 1997;Intachat et al 2001;Hamer et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Tropical insects show remarkable variation in their seasonal patterns (Wolda 1988). While the abundance of many species increases in the rainy season and decreases in the dry season (Wolda 1980, Wolda and Fisk 1981, Novotny and Basset 1998, an opposite pattern has been found in areas with very mild dry seasons (Janzen 1973, Hamer et al 2005. Populations of some other species fluctuate aseasonally (Grimbacher andStork 2009, Kishimoto-Yamada et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…More abundant species benefit from the wet season and grow in number until the T.wd. In this way, the response of the most abundant species could be associated with Previous studies have reported that forested habitat has great temporal species turnover, suggesting that habitat structure is an important factor in the temporal dynamics of butterflies (Shahabuddin & Terborgh 1999;Hamer et al 2005;Barlow et al 2008;DeVries et al 2011;Nobre et al 2012). The results of the present study agree with this hypothesis and indicate that the open habitat surveyed (i.e., savanna), in contrast to the forested habitat surveyed, is spatially less diverse and, as a consequence, has a butterfly assemblage that is more homogeneously distributed over the seasons (Hamer & Hill 2000;Hamer et al 2003).…”
Section: Figmentioning
confidence: 88%